PERTUMBUHAN TINGGI TANAMAN SAMBILOTO (Andrographis paniculata. Ness) HASIL PEMBERIAN PUPUK DAN INTENSITAS CAHAYA MATAHARI YANG BERBEDA - MALIK, NURHAYU (Jurnal Agroteknos, 2014)
This study aimed to evaluate the effect of fertilization and different light intensities on growth of plant height of bitter plant (Andrographis paniculata Ness). The study was conducted using Completely Randomized Design (CRD) with 3 x 3 factorial pattern. The main factor was fertilization treatment consisted of three levels: NPK (Urea 1.2 grams per plant, TSP 2.4 g per plant and KCl 0.6 g per plant), animal manure (1.2 kg per plant) and without fertilization. The second factor was the different light intensities consisted of three levels: full light intensity, half-shade and full shade. Each treatment combination was repeated 3 times. Growth of plant height was observed 1 and 2 months after application of fertilizer and light intensity. Data were analyzed using the Analysis of Variance (Anova).The research results showed that bitter plant height differed at fertilization levels and different light intensities. NPK fertilization combined with 40 % light intensity (P2N1) gave the highest plant height.